Corticosteroids for Nerve Regeneration: A Narrative Review - Alsharif, Mohammed H. Karrar; Bakhit, Nagi M.; Almasaad, Juman M.; Önger, Mehmet Emin (Current Pharmaceutical Design, 2026)
Despite the use of advanced microsurgical techniques, around one-third of peripheral nerve injuries still show inadequate functional regeneration and incomplete healing. Peri- and intraneural nerve damage leads to pathophysiologic alterations, including morphological and metabolic changes, where the nerve is disrupted. Animal research shows no proven adjustment drugs for peripheral nerve regeneration, but studies suggest medicines can speed up regeneration using functional and histological parameters after nerve injury. Factors affecting nerve regeneration effectiveness include injury type, age, regeneration time, procedures, and materials. Complete regeneration and functional recovery are rarely achieved, regardless of the kind of pharmaceutical therapy used, necessitating further research into nerve regeneration. Future research could enhance corticosteroid doses with additional drugs, increasing clinical use. This review explores the mechanism of action of corticosteroids Dexamethasone, Betamethasone, and Methylprednisolone in peripheral nerve regeneration experiments, highlighting the potential for enhanced nerve injury.
Keywords: central nervous system